(untitled) (International Journal of Food and Nutritional Sciences, 2022)
An edible vaccine is a pharmaceutical product derived from antigens expressed in transgenic plants. This concept, introduced in the 1990s and developed by Dr. Charles Arntzen, represents a novel approach to oral immunization that has the potential to save millions of lives, particularly in countries where vaccination against infectious diseases is crucial. Edible vaccines function as preventive measures rather than treatments. They are cost-effective, easy to administer, and widely accepted as vaccine delivery systems, particularly beneficial for economically disadvantaged developing nations. It is estimated that edible vaccines may become mainstream medical products within 10-20 years. The future of this research hinges on public acceptance and willingness to use recombinant plants without fear.